2021
DOI: 10.1002/nau.24861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of levator ani muscle contraction on post‐prostatectomy urinary incontinence using cine MRI

Abstract: Post-prostatectomy urinary incontinence (PPI) is the greatest concern for urologists after radical prostatectomy (RP). It is thought that PPI is composed of multiple factors including static and dynamic components. The purpose of this study is to show visually levator ani muscle (LAM) contraction during pelvic floor muscle contraction and to evaluate the dynamic differences in its contraction between men with and without PPI.Methods: This study was a case-control study of the urinary continent or incontinent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The PB-AR during abdominal pressure is thought to move in the direction of shortening (positive distribution) and UVJ movement in the cephalic direction (zero to negative distribution) when PFMT are effective in urinary continence, and these movements are reportedly effective in urinary continence 8 , 9 , 11 . Several RCTs have been conducted on the effect of PFMT on reducing urinary incontinence after RP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PB-AR during abdominal pressure is thought to move in the direction of shortening (positive distribution) and UVJ movement in the cephalic direction (zero to negative distribution) when PFMT are effective in urinary continence, and these movements are reportedly effective in urinary continence 8 , 9 , 11 . Several RCTs have been conducted on the effect of PFMT on reducing urinary incontinence after RP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many anatomical studies that use magnetic resonance imaging (MRI) have reported that membranous urethral length (MUL) affects postoperative urinary continence, which may be related to resting urethral closure pressure 3 7 . The mechanism of SUI has also been investigated using transperineal ultrasound and dynamic MRI, and several studies reported on the relationship between pelvic anatomy changes during abdominal pressure and postoperative urinary incontinence 8 11 . Additionally, many surgical techniques have been reported to reduce postoperative urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of urethral closure during abdominal pressure has been observed in the pre-RP state, as well as in studies using transperineal ultrasound and dynamic MRI. The anterior wall of the rectum is reported to move in the direction of the pubic bone simultaneously with the applied abdominal pressure, and it is thought that this is observed mainly because the urethra is compressed in the anterior-posterior direction by the action of the levator ani muscle, resulting in increased pressure at urethral closure [61,62]. In a report examining pelvic anatomical changes during abdominal pressure after RP, the anterior wall of the rectum moved less toward the pubic bone than before RP, which is thought to affect the urethral sphincter closure pressure, resulting in an increased probability of stress urinary incontinence [62,63].…”
Section: Mechanism Of Urinary Incontinence After Radical Prostatectomymentioning
confidence: 99%
“…The anterior wall of the rectum is reported to move in the direction of the pubic bone simultaneously with the applied abdominal pressure, and it is thought that this is observed mainly because the urethra is compressed in the anterior-posterior direction by the action of the levator ani muscle, resulting in increased pressure at urethral closure [61,62]. In a report examining pelvic anatomical changes during abdominal pressure after RP, the anterior wall of the rectum moved less toward the pubic bone than before RP, which is thought to affect the urethral sphincter closure pressure, resulting in an increased probability of stress urinary incontinence [62,63]. In fact, the abdominal leak point pressure test shows that urine leakage during abdominal pressure, which was rarely observed preoperatively, is observed in an increasing number of cases after RP, indicating that a decrease in urethral closure pressure during abdominal pressure occurs after RP [58,60].…”
Section: Mechanism Of Urinary Incontinence After Radical Prostatectomymentioning
confidence: 99%
See 1 more Smart Citation